The Dao Admits of No Admixture Mysticism and Moral Realism in Zhuangzi's Writings - Sta. Maria, Joseph Emmanuel D. (Budhi: a Journal of Ideas and Culture, 2018)
Recent philosophical scholarship tends to cast Zhuangzi's philosophy as promoting moral relativism. This is especially true with Chad Hansen's interpretation of Zhuangzi's writings. †his article seeks to challenge this dominant relativist reading by showing that such a reading does not align with the numerous and evaluative remarks that can be found in Zhuangzi's work. Furthermore, this article aims to show that it is more plausible that Zhuangzi's metaethical view is that of moral realism instead of moral relativism. This is because a moral realist interpretation of Zhuangzi's philosophy fits more, not only with the aforesaid evaluative and normative of Zhuangzi's writings, but also with the mystical elements found in the same writings.